Colaboração premiada: legitimidade e procedimento - Pereira, Frederico Valdez (2011)
Collaboration rewarded directly inspired by Italian and American law also known as procedural collaboration or whistleblower reward, aims to contribute to the acquisition of investigative and evidentiary elements since investigation by traditional methods is blocked. The problem of strengthening methods of proof presents a possible conflict of interest in criminal justice s efficiency with rights of freedom and maintenance of procedural dynamics vigor, leading us to reflection on the theme from criteria given theory of principles and proportionality. Therefore, it values the latent constitutional tension on this theme. Moreover, the greatest difficulty in positive law is that Brazilian legislation does not set procedural rules to whistleblower award, which makes it difficult mainly regarding what procedure to be taken, how to manage pentiti, and probative valuation of co-defendants statements that collaborate with Justice. Hence, it is addressed how collaboration rewarded can be legitimately used by courts, preserving both its purpose and the fundamental guarantees of those involved.